1,2,3-Triazole-Guided Multi-Component Sonogashira Coupling of Substituted Benzosuberenes Derived from Cedrus deodara Oil - Kumar, Ashish; Kumar, Mahender; Sharma, Poonam; Das, Pralay (Synthesis, 2024)
Herein, Sonogashira coupling at the vinyl bromide position of triazole-bearing benzosuberene has been introduced for the synthesis of potentially bioactive 1,2,3-triazole and conjugated enynes containing benzosuberene analogues. The instalment of triazole moiety on the allylic position dictates the Sonogashira coupling at the vinylic position, the absence of which failed to execute the desired reaction. The Cu-catalyzed cycloaddition initially led to the incorporation of 1,2,3-triazole, which subsequently directed the Pd/Cu-catalyzed Sonogashira coupling to deliver new class of benzosuberene analogues in appreciable yields. The regioselective synthesis of 1,2,3-triazole and conjugated enynes containing benzosuberene analogues has been reported under operationally simple and milder reaction conditions.
Keywords: Cedrus deodara oil; cycloaddition reaction; Sonogashira coupling; 1,2,3-triazoles synthesis; enynes synthesis; benzosuberene analogues